Image Paradigm “Song → Body” in Song Text Poetics (by Material of F. Kankulov’s Poetry Collection “Voice of the Heart”) - I. A. Kazharova; L. B. Berberova (Научный диалог)
The specificity of actualization of an image in the poetics of a song text is considered. Difficulties of theoretical interpretations of song genre as a form of literary creation are revealed, within its context the status of popular songs poetry is revealed. Questions of interaction of modalities of personal “I” of a poet-songwriter and audience for which he / she creates are touched. A distinction is made between the cases of “spontaneous” music transcription of texts that were originally created in the context of recitation poetry, and the cases of originally conceived, conscious projection of texts to music. Semantic regularities can be traced on concrete material, which determine the specificity of a song in the role of an image typical to mass songs genre. The paradigm “song → body” is considered as one ofthe variants of representation of this image. Examples are given from the song poetry by F. M. Kankulov, whose work to date has not attracted the attention of researchers, especially the individual aspects of his poetry, which determines the novelty of the presented observations, were not considered. The study suggests that the cultural specificity that emerges in the paradigm raises the question of new mental aspects in image reading, which within the song text is based on the upper, and therefore, the most transparent layers of cultural identity.